Governance in Dark Times : Practical Philosophy for Public Service. - Stivers, Camilla (Georgetown University Press, 2010)
With the rush of calamitous events in recent years--the September 11 terror attacks, the Iraq imbroglio, and hurricanes Katrina and Rita--Americans feel themselves to be living in dark times. Trust in one another and in the government is at low ebb. People in public service face profound challenges to the meaning and efficacy of their work. Where can a public servant turn for a public philosophy to sustain practice?Inspired by Hannah Arendt and several other philosophers, Governance in Dark Times is the first book to explore the philosophical and value underpinnings needed to guide public servan.